2013
DOI: 10.1155/2013/748405
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cone Beam Computed Tomography in Rehabilitation of a Traumatised Deficient Maxillary Alveolar Ridge Using Symphyseal Block Graft Placement

Abstract: Deficiencies in the alveolar ridges cause multiple problems in achieving aesthetic and functional outcome of implant therapy and are commonly restored by using onlay graft from intraoral source. Careful assessment of the recipient as well as the donor site using cone beam computed tomography (CBCT) is a prerequisite to ideal treatment planning. This paper highlights the critical role of CBCT in planning a successful rehabilitation of traumatised deficient anterior maxillary alveolar ridge using autogenous bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 9 publications
(18 reference statements)
0
11
0
3
Order By: Relevance
“…Of the previous studies investigating CBCT measurements, several have reported the importance of CBCT on the evaluation of buccal and lingual cortical bone thickness for mini-implant placement, to re-establish the buccal bone wall after immediate implant placement, and to detect bone defects. 2,3,13,17,[25][26][27][28] However, the use of CBCT for these applications should be optimized by balancing diagnostic image quality with radiation dose. The current results show that a 360-degree protocol may not show a distinct advantage over a 180-degree protocol, implying that the latter would be preferred because of its lower radiation dose (approximately 50% reduction).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the previous studies investigating CBCT measurements, several have reported the importance of CBCT on the evaluation of buccal and lingual cortical bone thickness for mini-implant placement, to re-establish the buccal bone wall after immediate implant placement, and to detect bone defects. 2,3,13,17,[25][26][27][28] However, the use of CBCT for these applications should be optimized by balancing diagnostic image quality with radiation dose. The current results show that a 360-degree protocol may not show a distinct advantage over a 180-degree protocol, implying that the latter would be preferred because of its lower radiation dose (approximately 50% reduction).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate information regarding the presence of cortical bone may prevent multiple aesthetic and functional problems in the outcome of implant therapy, independent of the bone thickness present. 17 Many image quality factors should be considered to explain the limitation of CBCT for this application. The spatial resolution can be considered the minimum distance necessary to distinguish 2 objects located closely together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies used to overcome mandibular atrophy include various techniques developed to increase bone volume, such as onlay/inlay bone grafting [ 6 8 ], GBR [ 9 , 10 ], ridge expansion [ 11 ], and distraction osteogenesis [ 7 , 12 ]. Although it has been shown that it is possible to augment bone with all these different techniques, each of these options poses a risk of complications or potential for dimensional graft loss [ 4 , 5 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different surgical techniques have been used to overcome alveolar ridge atrophy, including onlay/inlay bone grafting [ 6 8 ], guided bone regeneration (GBR) [ 9 , 10 ], ridge split technique/ridge expansion [ 11 ], and distraction osteogenesis [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%